Design and Implementation of a Low-Cost Remote-Controlled Glove Using Sensor Technology - Hussein, Mahdi abed; mahdi, Hussein abbas; abdulazahraa, Ali Adnan; abdulamir, Hussein mohammed; Shihab, Mudhafar Naseer (American Journal of Botany and Bioengineering, 2025)
The demand for remote control technologies is rising as applications requiring safety and convenience increase. The evolution of technology continually encourages the creation of diverse remote-control designs. This project focuses on designing and manufacturing a low-cost remote-controlled glove using sensor technology. The main objective is to develop a glove that facilitates remote control applications. To achieve this, it is essential to design a functional system, select appropriate sensors suitable for assembling the glove, and fabricate the final wearable prototype. Sensor technology plays a crucial role by enabling the glove to detect various human motions and convert them into controlled signals. The implemented system utilizes an Arduino microcontroller, a Bluetooth module for communication, power supply, and flex and accelerometer sensors. The system’s functionality has been thoroughly tested and verified through practical trials.